Critical factors influencing accounting firm management (AFM) satisfaction with accounting undergraduates: a review and conceptual framework - Hu, Guojing; Muhamad, Haslinah; Mustafa, Hasri; Liu, Man (Malque Publishing, 2024)
In the recruitment market, accounting employers prioritize the competency of graduates by developing policies to ensure their satisfaction. However, since accounting firms are the primary potential employers for accounting undergraduates, it is essential to investigate the satisfaction of accounting firm management (AFM) with the competency of graduates. Therefore, this study integrates human capital theory (HCT) and expectancy disconfirmation theory (EDT), considering the competency of accounting undergraduates as human capital, which serves as a key factor in assessing AFM satisfaction. Subsequently, the study introduces variables and path relationships derived from the European Customer Satisfaction Index (ECSI), outlining four key constructs: AFM expectation, AFM perceived quality, AFM perceived value, and AFM satisfaction. Previous research has shown that the application of the ECSI has expanded to the higher education field for measuring student satisfaction. Accordingly, in the context of accounting education, this study considers AFM to be the primary client and views the competency of accounting undergraduates as the product or service provided to the client. This study provides an overview of the previous theoretical and empirical literature and develops a conceptual framework aimed at assessing the factors influencing the satisfaction of accounting undergraduates with AFM. Additionally, it addresses gaps in the previous literature, laying the foundation for future research.